2003
DOI: 10.1038/sj.onc.1206563
|View full text |Cite
|
Sign up to set email alerts
|

Development of CD30+ lymphoproliferative disease in mice lacking interferon regulatory factor-1

Abstract: Human lymphomas continue to represent a major challenge in oncology, and in particular occur at very high frequencies in AIDS patients. We report here the development of a CD30 þ lymphoproliferative disease in mice lacking the proapoptotic transcription factor, interferon regulatory factor-1. These mice most closely represent a model of human anaplastic large-cell lymphoma (ALCL). This mouse model of lymphoma will likely be useful in understanding the development of ALCL and in understanding the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…The link between IRF‐1 and TRAIL provides a novel insight into molecular mechanisms by which IRF‐1 exerts its tumor suppressor activity in various systems (Tanaka and Taniguchi, 2000). Indeed, while initial gene deletion experiments suggested that IRF‐1 acted as a ‘tumor susceptibility gene’ (Nozawa et al , 1999), recent data obtained with older IRF‐1 −/− mice (Eason et al , 2003) and the frequent loss or epigenetic modification of the IRF‐1 locus in hematopoietic and solid cancers indicate that IRF‐1 is a bona fide tumor suppressor. The molecular basis underlying the tumor suppressive activity of IRF‐1 is still incompletely understood, albeit some features have been worked out.…”
Section: Discussionmentioning
confidence: 99%
“…The link between IRF‐1 and TRAIL provides a novel insight into molecular mechanisms by which IRF‐1 exerts its tumor suppressor activity in various systems (Tanaka and Taniguchi, 2000). Indeed, while initial gene deletion experiments suggested that IRF‐1 acted as a ‘tumor susceptibility gene’ (Nozawa et al , 1999), recent data obtained with older IRF‐1 −/− mice (Eason et al , 2003) and the frequent loss or epigenetic modification of the IRF‐1 locus in hematopoietic and solid cancers indicate that IRF‐1 is a bona fide tumor suppressor. The molecular basis underlying the tumor suppressive activity of IRF‐1 is still incompletely understood, albeit some features have been worked out.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicated that loss of IRF1 exacerbates previous tumor predisposition and most likely regulates tumor suppressor pathways independent of p53 [16]. In addition, another IRF1 −/− murine model revealed that loss of IRF1 results in a lymphoproliferative disease that mimics ALCL [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although many mouse-specific antibodies are commercially available for IHC in frozen tissue, cryostat sections are inferior in quality when compared to paraffin sections. During the last 20 years, pathologists engaged in the pathology of mice have been making efforts to apply immunohistochemistry in the diagnosis of mouse hematopoietic diseases (Fredrickson et al, 1985,1999; Frith et al, 1993; Ward et al, 1993; Qi et al 1998, 2000; Sabourin et al, 2000; Morse et al, 2001; Eason et al, 2003; Lange et al, 2003; Utsuyama and Hirokawa, 2003; Canela et al, 2004; Huang et al, 2004; Miyakawa et al, 2004; Neeson and Paterson, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although many mouse-specific antibodies are commercially available for IHC in frozen tissue, cryostat sections are inferior in quality when compared to paraffin sections. During the last 20 years, pathologists engaged in the pathology of mice have been making efforts to apply immunohistochemistry in the diagnosis of mouse hematopoietic diseases (Fredrickson et al, 1985(Fredrickson et al, ,1999Frith et al, 1993;Ward et al, 1993;Qi et al 1998Qi et al , 2000Sabourin et al, 2000;Morse et al, 2001;Eason et al, 2003;Lange et al, 2003;Utsuyama and Hirokawa,However, only 3 of the antibodies tested in that study are useful for the classification of murine hematopoietic neoplasms (Mikaelian et al, 2004). Therefore, the aim of this study was to develop a standardized panel of antibodies reactive in paraffin-embedded tissue, useful for the classification of hematopoietic tumors.…”
Section: Introductionmentioning
confidence: 99%